Analytical Study of Evidences & Signs of Prophecy of Muhammad (S.A.W) in Sharaf-al-Mustafā and Al-Shifā - Muhammad Rafiq; Hafiz Muhamad Sajjad (Journal of Islamic and Religious Studies, 2019)
In the status and degrees of spirituality, the highest ranking position is prophecy and apostleship in which a person gets free feeds and knowledge from the creator of the universe and then with this light and illumination brightens the hearts of other mankind. Indeed, it is an unusual claim that a prophet or a messenger does and in fact it requires strong evidences to prove. That’s why all prophets are awarded some qualities, discriminations, signs and evidences from Allah Almighty through which people clearly get awareness and acknowledgement. Such things are “Signs and Evidences of Prophecy” in which the greatest sign is “miracle”. The basic question of this article is that what are signs, evidences and arguments of prophecy in Sharaf-ul-Muṣṭafa and Al-Shifā? And what are their present implementation and importance? These books are famous for the dignity and rights of Prophet (S.A.W) and researched by scholars as a whole on their writers, contents, and methodology but not yet studied in this perspective. In this article few most important of them are selected and analyzed. Innocence and pure race, miraculous appearance, personality, debonairness, eloquence, stamp of prophet-hood, miracles and being illiterate etc. all are symptoms of prophecy of Muhammad (S.A.W). In contemporary situation the best way to prove truthfulness and greatness of Prophet (S.A.W) is to focus on better scientific, rational, logical and practical aspects of Muhammad’s (S.A.W) life and we have to apply it.